Growth, chemical, and biochemical composition of Conocarpus erectus L. in response to NPK fertilizers and extracts of active dry yeast, seaweeds, and green tea - El-Mahrouk, El-Sayed Mohamed; Mahmoud, Huda Gamal; Abdelaal, Khaled; Ebrahim, Hayam Mohamed Aly; El-Tarawy, Ahmed Mohamed; Alsakkaf, Waleed A. A.; Ahmed, Temoor; Ali, Hayssam M. (Frontiers in Plant Science, 2025)
Conocarpus erectus L. is one of the ornamental shrubs or trees that are utilized in different aspects in landscape (gardens, cities, roads, etc.). Fertilization program is an essential factor affecting the aesthetic characters of this plant species. Pots experiment was conducted in a randomized completed split plot design with the aim to study the effects of NPK fertilizers at the levels of 100%, 75%, and 50% of the suggested doses of 18, 12, and 6 g/plant from ammonium sulfate, calcium superphosphate, and potassium sulfate, respectively, as well as natural extracts as active dry yeast (ADY) at 1 or 3 g L-1, green tea (GT) at 0.2 or 0.5 g L-1, and seaweeds (SW) at 1 or 1.5 mL L-1, and their interaction on the growth and attributes of C. erectus in the 2022 and 2023 seasons. The results indicated that 100% NPK dose produced the highest significant values of plant height, number of branches, primary stem diameter, area/leaf, chlorophyll index, shoots and root fresh and dry weight, percentage of relative water content (in the second season), N, P, K, and total carbohydrates in comparison with 75% and 50% NPK doses in the both seasons. Moreover, 100% NPK increased the activity of peroxidase enzyme, phenol compounds, and antioxidant activity over the 75% and 50% NPK doses. Conversely, 75% NPK recorded a high relative water content (in the first season) and activity of catalase and polyphenol oxidase enzymes over the 100% and 50% NPK doses. All treatments of natural extracts had positive impacts on the studied parameters previously mentioned when compared to untreated control. Among the natural extracts used, 3 g L-1 ADY was the best application to increase the studied traits, except for leaf area and P%, whose higher significant values resulted from treatments with application of SW extract at 1.5 mL L-1 and 1 g L-1 ADY + 0.2 g L-1 GT + 1 mL L-1 SW, respectively. Moreover, the 100% NPK dose combined with 3 gL-1 ADY was the best combination to execute the highest values of the aforementioned traits studied, except the primary stem diameter, P%, and PPO activity, whereas the highest values resulted from treatments with 100% NPK dose + 1.5 mL L-1 SW, 1 g L-1 ADY + 0.2 g L-1 GT + 1 mL L-1 SW, and 75% NPK dose + 3 g L-1 ADY, respectively. Therefore, 100% NPK treatment combined with 3 g L-1ADY is recommended to fertilize C. erectus plants in order to reduce the overuse of chemical fertilizers and to minimize habitat contamination for the maintenance of the whole environment.